2020
DOI: 10.1007/s11418-020-01405-w
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Antiinflammatory constituents of Atractylodes chinensis rhizome improve glomerular lesions in immunoglobulin A nephropathy model mice

Abstract: The article Antiinflammatory constituents of Atractylodes chinensis rhizome improve glomerular lesions in immunoglobulin A nephropathy model mice, written by Toshinari Ishii, Tetsuya Okuyama, Nao Noguchi, Yuto Nishidono, Tadayoshi Okumura, Masaki Kaibori, Ken Tanaka, Susumu Terabayashi, Yukinobu Ikeya and Mikio Nishizawa was originally published Online First without Open Access. After publication in volume 74 issue 1, page 51–64 the author decided to opt for Open Choice and to make the article an Open Access p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, ATL-III can reduce chronic kidney disease-induced inflammation and muscle atrophy by inhibiting the PI3K-Akt pathway (Wang et al, 2019). And then, ATL-III also reduces the production of proinflammatory mediators NO, reduces the levels of TNF and IL, and then relieves the damage to renal cells (Ishii et al, 2020). Therefore, rhizoma Atractylodis has been used for clinical prevention and treatment of renal injury after Covid-19 infection (He et al, 2020).…”
Section: Atractylodesmentioning
confidence: 99%
“…Furthermore, ATL-III can reduce chronic kidney disease-induced inflammation and muscle atrophy by inhibiting the PI3K-Akt pathway (Wang et al, 2019). And then, ATL-III also reduces the production of proinflammatory mediators NO, reduces the levels of TNF and IL, and then relieves the damage to renal cells (Ishii et al, 2020). Therefore, rhizoma Atractylodis has been used for clinical prevention and treatment of renal injury after Covid-19 infection (He et al, 2020).…”
Section: Atractylodesmentioning
confidence: 99%
“…Paeoniflorin [4] and isoliquiritigenin [5] are widely known to have hepatoprotective potential. Furthermore, glycyrrhizin, another component of Glycyrrhizae Radix [6], and a certain fraction of Sojyutu extract [7] have been reported…”
Section: Introductionmentioning
confidence: 99%
“…The main bioactive compounds in A. chinensis rhizome are used to treat digestive disorders, rheumatic diseases and night blindness [ 6 ]. Modern pharmacological studies have demonstrated that A. chinensis also has anti-inflammatory, anti-bacterial [ 11 , 20 ] and antitumor [ 13 ] properties. Although the sesquiterpenoid components of A. chinensis rhizome have important pharmacological activities, the molecular mechanisms underlying accumulation of bioactive sesquiterpenoids are poorly understood.…”
Section: Introductionmentioning
confidence: 99%